Synthesis of biocompatible polymeric nanomaterial dually loaded with paclitaxel and nitric oxide for anti-MDR cancer therapy. Issue 107 (7th November 2016) - Fan, Jing; Song, Jibin; Liu, Yijing; Yu, Guocan; Ma, Ying; Deng, Yan; He, Nongyue; Zhang, Fuwu
Abstract : A copolymer nanomedicine mPEG–PEI–PLLA–PTX–NO was synthesized and studied in an OVCAR-8/ADR MDR cancer model. Abstract : Nitric oxide (NO) as a chemosensitizer has attracted a lot of attention in anti-multidrug resistance (MDR) tumor therapy. In this study, a three-segment amphiphilic copolymer was synthesized through click reaction by azido and alkyne groups. The PEI part with abundant secondary amines was utilized to load NO gas molecules, the hydrophobic PLLA core to encapsulate the hydrophobic drug paclitaxel (PTX), and the mPEG shell to provide a hydrophilic interface and lead the copolymer to self-assemble into micelles in the water phase for biological applications. This multifunctional mPEG–PEI–PLLA–PTX–NO nanostructure is able to release NO spontaneously under physiological conditions and enhance the cytotoxicity for synergistic treatment of PTX and NO, demonstrating the potential to treat MDR tumors.